Description of Scientific Normality, Attitudes of Investigation and Interested Career On Physics in Senior High School - Astalini Astalini; Dwi Agus Kurniawan; Deti Kurnia Sari; Wawan Kurniawan (STKIP Singkawang, 2019)
The purpose of this study was to determine the description of students' attitudes towards physics in Senior High School 8 Jambi City of Indonesia. This research is quantitative-qualitative research with survey research procedures. The subjects of this study were 170 students. The instruments used were questionnaires and interview sheets. Quantitative data analysis using descriptive statistics while qualitative data analysis using data analysis techniques model Miles and Huberman. The results of the 3 aspects of attitude indicators discussed in this study are on the indicator of normality of scientists as much as 60% are categorized quite good. While the attitude towards investigation in physics is 51% in the good category. Then in the indicator of interest in a career in the field of physics as much as 58% of students are categorized well.